Pola Pengelolaan Kekayaan Nagari Dan Pemberdayaan Masyarakat Dalam Peningkatan Kesejahteraan - Lerri Pattra (Faculty of Law, Andalas University, 2021)
One of the objectives of a state is stated in the fourth paragraph of the preamble to the 1945 Constitution, namely for the welfare of the community. After the enactment of the Regional Government Law, regional governments were given the authority to regulate and manage their own regional government affairs. The existence of nagari as a legal community unit in the Unitary State of the Republic of Indonesia has a constitutional basis in Article 18 B paragraph (2) of the 1945 Constitution, the article states